2018
DOI: 10.21776/ub.jtp.2018.019.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antioksidan, Sifat Fisik Dan Sensoris Es Krim Dengan Penambahan Sari Apel

Abstract: Penelitian ini bertujuan untuk mengetahui proses pembutan, formulasi, aktivitas antioksidan, sifak fisik, dan sensoris es krim dengan penambahan sari buah apel agar tercipta produk es krim yang baik dengan faktor penambahan sari apel sebesar 0%; 25%; 50%; dan 75%. Rancangan Acak Lengkap (RAL) dengan 5 kali pengulangan digunakan dalam penelitian ini. Data yang diperoleh dianalisis dengan cara menguji langsung sampel sebanyak 2 perlakuan dengan masing-masing perlakuan menggunakan 2 pengulangan untuk aktivitas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
1
1
6
Order By: Relevance
“…Secondary antioxidants are antioxidants that are not produced naturally by the human body and are obtained through dietary sources of antioxidants (Chauliyah and Murbawani, 2015). The antioxidant activity of the control treatment in this study was much higher than previous studies by Khairina et al (2018) that found an increase in the antioxidant activity along with the addition of apple cider into the ice cream. Also, in line with increasing antioxidant activity in ice cream after addition of lontar palm (Borassus flabeliffer L.) by Idayati et al 2019, and lemongrass juice with the different types of milk (Triastini, 2018).…”
Section: Antioxidant Activitycontrasting
confidence: 69%
“…Secondary antioxidants are antioxidants that are not produced naturally by the human body and are obtained through dietary sources of antioxidants (Chauliyah and Murbawani, 2015). The antioxidant activity of the control treatment in this study was much higher than previous studies by Khairina et al (2018) that found an increase in the antioxidant activity along with the addition of apple cider into the ice cream. Also, in line with increasing antioxidant activity in ice cream after addition of lontar palm (Borassus flabeliffer L.) by Idayati et al 2019, and lemongrass juice with the different types of milk (Triastini, 2018).…”
Section: Antioxidant Activitycontrasting
confidence: 69%
“…Ice cream with a high overrun value will result in a faster melt ice cream. This is due to a rise in air phase and it will form a lot of air space which will release simultaneously with ice crystal during melting [34]. A high viscosity value will result in a longer melting time of ice cream.…”
Section: Melting Timementioning
confidence: 99%
“…Coronavirus merupakan virus baru penyebab penyakit COVID-19, yang pertama kali ditemukan pada akhir tahun 2019 di Kota Wuhan, Provinsi Hubei, China. Ber-dasarkan situasi global pada tanggal 18 Senyawa andrographolide memiliki sifat aktivitas biologis seperti antiinflamsi, antikanker, antiobesitas, antidiabetes, antimikroba dan antivirus. Kandungan andrographolide terbanyak ditemukan pada di bagian daun yaitu sebesar 4.686% (4).…”
Section: Pendahuluanunclassified